The Semantic And Rhetorical Effects Of The Difference In Grammatical Aspects In The Qur’anic Sentence/ الآثار الدلالية والبلاغية لاختلاف الوجوه الإعرابية في الجملة القرآنية - El-Sharkawy, Mohammed Shehata Abdel-Hamid; Mohamed, Abdelkarim Ahmed Maghawry; Bakhet, Mohamed Ibrahim Mohamed; Issa, Koussoube; Salem, Elsayed Mohamed (Ijaz Arabi Journal of Arabic Learning, 2025)
This study discusses the variations in Arabic grammatical parsing in Surah Al-Imran and its semantic and rhetorical effects. This study aims to show the close relationship between parsing, meaning, and rhetoric by examining verses with various grammatical interpretations and the vast semantic range in Arabic, especially in the Quran. We can obtain extraordinary and profound meanings from changes in vowel marks, pauses, or specific interpretations; this research has numerous examples. The importance of this study lies in understanding and reflecting on the Quran and understanding its meaning through the science of Quranic parsing, adding new meanings through variations in parsing. The researchers used the inductive analysis method in this study, and the study results showed that the science of grammar and parsing are the foundations that build the Arabic language. Understanding the verses of the Quran, explaining their meanings, and explaining the connotations and rhetorical aspects intended requires knowledge of parsing and differences in parsing lead to differences in meaning.